Dynamics of Living Law, Legal Pluralism, and the Challenges of Codifying Customary Law in Indonesia's National Legal System - Titus Redisman Zebua (Journal of Political Innovation and Analysis, 2026)
Background: The recognition of living law and legal pluralism in Indonesia's national legal system has become increasingly urgent, illustrated by a viral TikTok case in which derogatory content toward the Dayak people triggered a customary tribunal convened by indigenous youth organizations across fourteen districts in West and Central Kalimantan. Objective: this study examines the nature of living law as a cultural phenomenon, how two normative systems negotiate within the same social space, and what is at stake when the state codifies customary law. Method: this study employs a qualitative legal anthropology approach through a descriptive-analytical case study design, drawing on library research and document analysis of legislation and literature, analyzed through phenomenological, theoretical, and critical-reflective interpretive stages. Results: the study finds that the recognition of living law in the National Penal Code (Law No. 1/2023, Article 2) marks a significant legal advancement, though top-down codification risks turning customary law into a static, inflexible artifact. Implications: theoretically, this study integrates living law, legal pluralism, politics of recognition, and restorative justice into a unified anthropological framework for digital-space jurisdictional conflict; practically, it recommends that the state adopt a protective rather than colonizing role, allowing living law to develop organically through communal deliberation and participatory governance.